Pancreatic herniation: a large pancreatic mass concealed within the intrathoracic cavity. Issue 7 (25th July 2022) - Karan, Abhinav; Kiamos, Amy; Stack, Anthony; Gharia, Bharatsinh
Abstract : Cancer of unknown primary is a challenging entity. We present an elderly woman with metastatic cancer of unknown primary despite comprehensive imaging and immunohistochemical analysis. Based on a thorough history, a gastrointestinal source was suspected and a diagnosis of pancreatic cancer concealed within a type IV hiatal hernia was made using multimodal imaging. On review of prior imaging, due to the highly complex anatomy within our patient's hiatal hernia, the pancreatic mass was retroactively noted. While initial imaging may detect metastatic disease, identifying the primary malignancy requires a thorough history and physical examination, multimodal imaging where malignancy is suspected, and immunohistochemical analysis of metastatic deposits. Herniation of pancreatic cancer has not been previously described in the literature and serves as an important reminder of the importance of multimodal imaging in patients with significantly complex anatomy.